The grey zone [videorecording (DVD)] - Nelson, Tim Blake; Arquette, David; Benzali, Daniel; Buscemi, Steve, 1957-; Chandler, David, 1950-; Corduner, Allan; Keitel, Harvey; Lyonne, Natasha; Sorvino, Mira; Nelson, Tim Blake (Lions Gate, 2002)
"Chronicles a unit of Auschwitz [II]'s Sonderkommando, a special squad of Jewish prisoners, who staged the only armed revolt that would ever take place at Auschwitz"--Container.